2004
DOI: 10.1128/jcm.42.3.1308-1312.2004
|View full text |Cite
|
Sign up to set email alerts
|

DifferentialIdentification of Mycobacterium tuberculosis Complexand Nontuberculous Mycobacteria by Duplex PCR Assay Using the RNAPolymerase Gene( rpoB )

Abstract: A novel duplex PCR method that can amplify the 235-and 136-bp rpoB DNAs of Mycobacterium tuberculosis complex and nontuberculous mycobacteria (NTM), respectively, with two different sets of primers was used to differentially identify 44 reference strains and 379 clinical isolates of mycobacteria in a single-step assay. Showing 100% sensitivity and specificity, the duplex PCR method could clearly differentiate M. tuberculosis complex and NTM strains. In addition, restriction fragment length polymorphism analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 22 publications
1
40
0
2
Order By: Relevance
“…Many regions of the mycobacterial genome have been used in molecular diagnosis of TB, such as IS6110, 16S rRNA, hsp65, rpoB, sdaA, devR and mpt64 (Manjunath et al, 1991;Lachnik et al, 2002;Kim et al, 2004;Chakravorty et al, 2005;Negi et al, 2007;Hwang et al, 2013;Nimesh et al, 2013). mpt64 is found as a single copy in the genome of MTBC species (Lee et al, 1994), and has been used for both pulmonary and extrapulmonary TB diagnosis (Tan et al, 1995;Dar et al, 1998;Martins et al, 2000;Bhanu et al, 2005;Therese et al, 2005;Takahashi & Nakayama, 2006;Dil-Afroze et al, 2008;Kusum et al, 2012;Sethi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Many regions of the mycobacterial genome have been used in molecular diagnosis of TB, such as IS6110, 16S rRNA, hsp65, rpoB, sdaA, devR and mpt64 (Manjunath et al, 1991;Lachnik et al, 2002;Kim et al, 2004;Chakravorty et al, 2005;Negi et al, 2007;Hwang et al, 2013;Nimesh et al, 2013). mpt64 is found as a single copy in the genome of MTBC species (Lee et al, 1994), and has been used for both pulmonary and extrapulmonary TB diagnosis (Tan et al, 1995;Dar et al, 1998;Martins et al, 2000;Bhanu et al, 2005;Therese et al, 2005;Takahashi & Nakayama, 2006;Dil-Afroze et al, 2008;Kusum et al, 2012;Sethi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…La faible variabilité des séquences d'ARNr 16S rend également confuse la limite des genres et des espèces bactériennes. De nouveaux marqueurs phylogénétiques : gyrB (gyrase) [5], rpoB (ARN polymérase) [6], hsp60 (heat-shock protein) [7]… ont été proposés en association à l'ARNr 16S pour la caractérisation de certaines espèces et genres bactériens cultivables. Ils devront être évalués pour la détection des bactéries non cultivables.…”
Section: L'approche Moléculaire Aujourd'huiunclassified
“…Relancer la recherche de nouvelles molécules à haute valeur ajoutée Sachant que 70 % des antibiotiques actuels sont produits par moins de 1 % des bactéries cultivables actuellement réperto-riées 6 , l'accès à la microflore de différents écosystèmes repré-sente une ressource biologique potentiellement inépuisable. L'utilisation des micro-organismes non cultivables (non cultivés) pour le développement de nouveaux produits à haute valeur ajoutée commence à voir le jour.…”
Section: Acquérir De Nouvelles Connaissances Grâce à La Génomiqueunclassified
“…This mutation can be found in 96.1% of rifampicin resistant M. tuberculosis isolates and occurs in rifampicin resistancedetermining region with 81-bp lengths corresponding to 507 -533 amino acid residues (35). In an Iranian report, it was demonstrated that 28% of isolates were rifampicin resistant, which was still lower compared to many areas in Africa and Europe (51.9% -68.9%) (36), while in the United States, about 13% of isolates from new tuberculosis cases have been resistant to one or more of the first-line antituberculosis drugs and 1.6% of cases are resistant to both isoniazid and rifampicin, defined as multidrug-resistant tuberculosis (37). Although multidrug-resistant tuberculosis in the re-treatment patients varies from 30% to 80% in different regions of the world (38), a study in Iran showed a notable success in the treatment of multidrug-resistant tuberculosis (39).…”
Section: Treatment Policy and Antibiotic Resistancementioning
confidence: 99%